2016
DOI: 10.1016/j.rboe.2015.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Intraosseous anomalous drainage: a rare case of pretibial varicose vein

Abstract: Valve failure with reflux and post-thrombotic syndrome are the factors most commonly correlated with varicose disease. Other rare etiologies can be put forward when these two main causes are ruled out. We report a case in which a young man presented chronic pain in the left tibia, varicose veins in the lower limbs and frequent occurrences of erysipelas. During investigation of the etiology of the varicose veins, radiographs and magnetic resonance imaging of the left leg were requested. These showed images sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The canals may be dilated in case of varices, vascular deformity, or adjacent tumor. 28,29 The exact vascularization of long bones and particularly of the cortices is controversial, 30,31 but micro-CT studies showed that numerous very narrow canals cross the cortex, contributing to intracortical porosity, increasing the risk and extension of microcracks. 32 Canal size, inclination, and spatial distribution (endosteal or periosteal, lateral, medial, anterior, or posterior cortex) vary in normal cases, affecting the cortex's mechanical resistance to stress.…”
Section: Diaphyseal Contours Cortical Vascular Canalsmentioning
confidence: 99%
“…The canals may be dilated in case of varices, vascular deformity, or adjacent tumor. 28,29 The exact vascularization of long bones and particularly of the cortices is controversial, 30,31 but micro-CT studies showed that numerous very narrow canals cross the cortex, contributing to intracortical porosity, increasing the risk and extension of microcracks. 32 Canal size, inclination, and spatial distribution (endosteal or periosteal, lateral, medial, anterior, or posterior cortex) vary in normal cases, affecting the cortex's mechanical resistance to stress.…”
Section: Diaphyseal Contours Cortical Vascular Canalsmentioning
confidence: 99%
“…Because intraosseous venous drainage can cause venous valvular insufficiency by increasing venous pressure [6], caution is needed when evaluating pretibial varices even if there is definite truncal valvular insufficiency. Familiarity with the characteristic triad of these lesions will be helpful for the diagnosis: (1) symptom-producing pretibial varices, (2) a cortical defect in the anterior aspect of the mid-tibia, and (3) an enlarged intraosseous vein and nutrient canal [3].…”
mentioning
confidence: 99%